The readiness of HR practitioners to address the influence of the Fourth Industrial Revolution on employee wellbeing : an exploratory study - Coetzee, Debbie (Stellenbosch : Stellenbosch University, 2024)
Thesis (MCom)--Stellenbosch University, 2024.